Exploring the Dimensions of Motivation in Stroke Survivors During Physical Rehabilitation: A Qualitative Inquiry - Flores Carrera , Stephanie; Saadati, Seyed Amir (KMAN Counseling & Psychology Nexus, 2025)
The objective of this study was to explore the dimensions of motivation in stroke survivors during physical rehabilitation, focusing on the personal, social, and environmental factors that shape engagement and recovery. This qualitative study employed an exploratory design to investigate motivational experiences of stroke survivors. Twenty participants (11 men and 9 women, aged 38–72) were recruited purposively from rehabilitation centers across the United States. Semi-structured interviews were conducted, each lasting 45–75 minutes, and data collection continued until theoretical saturation was reached. Interviews were audio-recorded, transcribed verbatim, and analyzed using thematic analysis with NVivo 14 software. Coding was carried out iteratively, with two researchers independently coding transcripts to ensure reliability, followed by consensus meetings to finalize themes. Three overarching themes emerged from the data. The first, personal and psychological factors, encompassed subthemes such as sense of purpose, emotional resilience, self-efficacy, coping strategies, identity reconstruction, and cognitive engagement. The second, social and relational support, included family encouragement, peer interaction, professional support, community involvement, and social recognition. The third, rehabilitation environment and external influences, comprised therapeutic setting, individualized programs, technological aids, physical and financial barriers, healthcare policies, reward systems, and environmental stimuli. Participants described motivation as a dynamic construct shaped by internal beliefs, relational networks, and systemic conditions, with direct quotations illustrating these lived experiences. The findings demonstrate that motivation in stroke rehabilitation is multidimensional, integrating psychological, social, and environmental domains. Recognizing and addressing these interconnected factors can enhance rehabilitation engagement, optimize functional outcomes, and promote holistic recovery. The study underscores the need for patient-centered, socially embedded, and technologically supported rehabilitation strategies.